2011
DOI: 10.1111/j.1365-3040.2011.02317.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of basal defence responsiveness in accessions of Arabidopsis thaliana

Abstract: Basal resistance involves a multitude of pathogen-and herbivore-inducible defence mechanisms, ranging from localized callose deposition to systemic defence gene induction by salicylic acid (SA) and jasmonic acid (JA). In this study, we have explored and dissected genetic variation in the responsiveness of basal defence mechanisms within a selection of Arabidopsis accessions. Responsiveness of JA-induced PDF1.2 gene expression was associated with enhanced basal resistance against the necrotrophic fungus Plectos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 92 publications
(194 reference statements)
0
31
0
Order By: Relevance
“…Consistent with this, we found that JA induces RGL3 expression to a substantially higher level in Can-0 and Sf-2 than in Col-0 and that the basal level of primary JA-responsive gene transcripts is also higher and is induced to higher levels by JA in Sf-2 than in Col-0 (see Supplemental Figure 8 online). Interestingly, the Sf-2 accession was recently reported to be naturally more resistant to various pathogens, including the necrotrophic fungus Plectosphaerella cucumerina (Ahmad et al, 2011). Results from our study raise the possibility that DELLA gene duplication events (that probably occurred after the divergence between dicots and monocots) increase the plasticity and the adaptation of plants to their surrounding growth conditions.…”
Section: Discussionmentioning
confidence: 53%
“…Consistent with this, we found that JA induces RGL3 expression to a substantially higher level in Can-0 and Sf-2 than in Col-0 and that the basal level of primary JA-responsive gene transcripts is also higher and is induced to higher levels by JA in Sf-2 than in Col-0 (see Supplemental Figure 8 online). Interestingly, the Sf-2 accession was recently reported to be naturally more resistant to various pathogens, including the necrotrophic fungus Plectosphaerella cucumerina (Ahmad et al, 2011). Results from our study raise the possibility that DELLA gene duplication events (that probably occurred after the divergence between dicots and monocots) increase the plasticity and the adaptation of plants to their surrounding growth conditions.…”
Section: Discussionmentioning
confidence: 53%
“…PAMPs are generally highly conserved among diverse microbial species (Boyd et al, 2013). Two RLK examples have been described which confer non-host resistance to Psph in A. thaliana , including FLS2 which enables detection of flagellin (Forsyth et al, 2010; Ahmad et al, 2011). In P. vulgaris , RLKs on Pv01 and Pv08 have been identified as candidates for race-specific resistance to anthracnose caused by Colletotrichum lindemuthianum (Burt et al, 2015; Zuiderveen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We found IRM1 expression to be suppressed in Col-0 upon aphid infestation whereas in WS it was initially induced, but suppressed afterwards. Such differences may result from the genetic differences among the two A. thaliana ecotypes in the basal defence to aphids [35].…”
Section: Discussionmentioning
confidence: 99%